Correction: The effects of marine traffic on the behaviour of Black Sea harbour porpoises (Phocoena phocoena relicta) within the Istanbul Strait, Turkey. - Aylin Akkaya Bas; Fredrik Christiansen; Ayaka Amaha Öztürk; Bayram Öztürk; Caley McIntosh (PLoS ONE, 2017)
[This corrects the article DOI: 10.1371/journal.pone.0172970.].